Study of Pineapple Juice Addition Towards Physicochemical Characteristics and Consumer Acceptability of Soyghurt - Nur Phi Lintang Kamulyan Sulityo; Masayu Nur Ulfa; Syahrizal Nasution (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to analyze the effect of adding pineapple juice at different concentrations on the viscosity, total solids, total dissolved solids, color, and consumer acceptance of soygurt. Methodology: A Completely Randomized Design (CRD) was used in this study, with the independent variable being the variation in the concentration of added pineapple juice (0%, 5%, 10%, 15%). Results: The results show that viscosity, total solids, total dissolved solids, and color are significantly influenced by the addition of pineapple juice. Findings: The consumer acceptance test indicated that the treatment with 10% pineapple juice had the best organoleptic value and was well accepted by consumers, with an average score of 4.11. Novelty: This research explores the enhancement of soygurt by adding pineapple juice, a novel approach to improving its taste and consumer appeal. Originality: The study provides a detailed analysis of the physicochemical and sensory characteristics of soygurt enhanced with pineapple juice. Conclusions: Adding pineapple juice to soygurt significantly improves its viscosity, total solids, total dissolved solids, and color, with 10% being the most favorable concentration for consumer acceptance. Type of Paper: Empirical Research Article